Biomimetic RBC-membrane-cloaked Prussian blue nanoparticles for synergistic photothermal-antibacterial therapy and accelerated wound healing - Xiaoyuan Ding; Haohao Wang; Fan Liu; Yan Wang; Leilei Gao; Fang Yang; Dong Liu (Materials & Design)
Delayed wound healing in infected wounds is primarily hindered by bacterial infections, posing significant physical and psychological burdens on patients. Exploring effective antimicrobial strategies is crucial for targeting bacterial infections and mitigating drug resistance. In this study, we developed biomimetic nanoparticles by loading the antimicrobial agent ergosterol onto Prussian blue nanoparticles (PB NPs) and encapsulating them with red blood cell membranes, which abbrieviated as RBC@PB-E. In vitro antimicrobial assays demonstrated that RBC@PB-E generated reactive oxygen species (ROS) and heat under near-infrared (NIR) irradiation, enhancing bacterial thermosensitivity and disrupting bacterial biofilms and cell membranes. Transcriptome analysis of infected wounds revealed that RBC@PB-E reduced the expression of inflammatory factors. In vivo studies showed that RBC@PB-E exhibited prolonged circulation and effectively accumulated at infection sites after intravenous injection. The photothermal effects of PB NPs combined with the membrane-disrupting capability of RBC@PB-E facilitated ergosterol penetration into bacteria under NIR irradiation. This resulted in excellent antibacterial efficacy in a MRSA wound infection model.In conclusion, the multifunctional photothermally activated antimicrobial nanoplatform RBC@PB-E provides a promising approach for combating bacterial infections and promoting wound healing.